Acciones de enfermería en prevención del pie diabético y su relación con la calidad de vida de adultos mayores con diabetes mellitus tipo 2. Centro de Salud #3 en la cuidad de Guayaquil, periodo junio - octubre 2023. - Macias Moreira, Joel Alejandro (2023)
Foot ulcers are among the major complications of diabetes, a complication that can lead to older adults being more prone to mobility disability due to non-traumatic lower limb amputation. The International Diabetes Federation (IDF) estimates that between 9.1 and 26.1 million people with diabetes will develop diabetic foot ulcers each year. In addition, type 1 and type 2 diabetics have a lifetime risk of foot ulcers of up to 34%. Epidemiological data indicate that diabetic patients have a 2.5% annual risk of developing foot ulcers. Aim: To determine nursing actions in diabetic foot prevention and their relationship to quality of life in older adults with diabetes mellitus. Methodology: The research is quantitative, descriptive, and documentary; Two observation guides were applied, one to review the patients' medical records and the second was aimed at observing nursing actions with these patients. Results: Of the 20 patients with diabetic foot complications in older adults with type II diabetes mellitus seen at Centro De Salud #3 in the period June - October 2023, the incidence was higher in the female sex (60%); in addition, the highest prevalence was in patients over 75 years of age (45%); the main risk factors were hypertension, obesity, and lack of care. In terms of nursing interventions, there is still room for improvement, but for the most part, they are being implemented.